Sex differences in navigation strategy and efficiency - Boone, Alexander P.; Gong, Xinyi; Hegarty, Mary (Memory & cognition, 2018)
Research on human navigation has indicated that males and females differ in self-reported navigation strategy as well as objective measures of navigation efficiency. In two experiments, we investigated sex differences in navigation strategy and efficiency using an objective measure of strategy, the dual-solution paradigm (DSP; Marchette, Bakker, & Shelton, 2011 ). Although navigation by shortcuts and learned routes were the primary strategies used in both experiments, as in previous research on the DSP, individuals also utilized route reversals and sometimes found the goal location as a result of wandering. Importantly, sex differences were found in measures of both route selection and navigation efficiency. In particular, males were more likely to take shortcuts and reached their goal location faster than females, while females were more likely to follow learned routes and wander. Self-report measures of strategy were only weakly correlated with objective measures of strategy, casting doubt on their usefulness. This research indicates that the sex difference in navigation efficiency is large, and only partially related to an individual’s navigation strategy as measured by the dual-solution paradigm.